2017
DOI: 10.5194/gmd-2017-105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A prognostic pollen emissions model for climate models (PECM1.0)

Abstract: Abstract. We develop a prognostic model of Pollen Emissions for Climate Models (PECM) for use within regional and global climate models to simulate pollen counts over the seasonal cycle based on geography, vegetation type and meteorological parameters. Using modern surface pollen count data, empirical relationships between prior-year annual average temperature and pollen season start dates and end dates are developed for deciduous broadleaf trees (Acer, Alnus, Betula, Fraxinus, Morus, Platanus, Populus, Quercu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…4.3). It has been reported that wind-driven pollen production has increased historically and is expected, potentially, to increase in the near future (R. Zhang et al, 2014;Lake et al, 2017;Confalonieri et al, 2007;Ziello et al, 2012). Some of more effective improvements to the emissions model would be to create a pollen production model that is sensitive to multiple environmental factors such as soil moisture, temperature, and nutrient status (Jochner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4.3). It has been reported that wind-driven pollen production has increased historically and is expected, potentially, to increase in the near future (R. Zhang et al, 2014;Lake et al, 2017;Confalonieri et al, 2007;Ziello et al, 2012). Some of more effective improvements to the emissions model would be to create a pollen production model that is sensitive to multiple environmental factors such as soil moisture, temperature, and nutrient status (Jochner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al, 2015a). Only recently have regional-scale modeling studies of pollen dispersion been conducted for Europe, and they have been used to assess the impacts of climate change on airborne pollen distributions (Sofiev and Prank, 2016;Lake et al, 2017). In contrast to most meteorological pollen models, climate models require long-term (e.g., decadal-to century-scale) emissions at a range of resolutions covering continental regions up to the global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Pollen input from external regions depends on the quantity of pollen produced and its transport to the study area. Oaks are very abundant in forests across much of the United States and are expected to be some of the most prolific producers of pollen on a national scale (Wozniak and Steiner, 2017), potentially leading to relatively high external inputs of oak pollen. In cities, absolute oak abundance is low to moderate (Pennington et al, 2010;White et al, 2014;Woodall et al, 2010), potentially resulting in a relatively lower ratio of local to external pollen compared to other genera.…”
Section: Airborne Pollenmentioning
confidence: 99%
“…One potential source of variation in pollen concentrations is the timing of flowering (Devadas et al, 2018). Phenology (the timing of life history events) has been well studied (Polgar and Primack, 2011), and the flowering of temperate trees primarily depends on temperature although precipitation and photoperiod can play important roles (Gerst et al, 2017;Ibáñez et al, 2010;Wozniak and Steiner, 2017). Temperature is generally higher in urban areas than surrounding rural areas; the urban heat island effect is widespread and has been documented extensively (Imhoff et al, 2010;Rizwan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, the Biogenic Emission Inventory System was adapted to emit birch and ragweed pollen and predicted the timing of the birch pollen peak to within two days (Efstathiou et al, 2011). Wozniak and Steiner (2017) modelled pollen from 13 different taxa based on plant functional type mapping for the USA, which could be used on climatic timescales. In Europe, Helbig et al (2004) simulated hazel and alder pollen emissions and transport across Germany, but did not verify their predictions as no pollen measurements were available.…”
Section: Introductionmentioning
confidence: 99%